Exploration of fast ion diffusion kinetics in graphene nanoscrolls encapsulated CoSe2 as advanced anode for high-rate sodium-ion batteries. (30th August 2021) - Zhang, Zhigang; Lin, Jun; Hao, Junyang; Xue, Fangfang; Gu, Yuefeng; Zhu, Zhicheng; Li, Qiuhong
Abstract: Sodium-ion batteries (SIBs) have drawn much attention due to the abundance and low cost of sodium. However, electrode materials of SIBs displayed sluggish Na + diffusivity and fatal volume expansion, owing to the larger ionic radius of Na + ions than Li + ions. In this work, we built the CoSe2 nanoparticles embedded in graphene nanoscrolls (GNS) as advanced anodes for high-rate SIBs. The CoSe2 /C@GNS anodes exhibited a high reversible capacity of 545 mA h g −1  at 0.2 A g −1 . Moreover, they showed an outstanding cycling stability of 455 mA h g −1 after 5000 cycles at 1 A g −1, with a capacity retention of 92% calculated from 10th cycle. The CoSe2 /C@GNS anode also demonstrate ultrahigh rate capabilities (212.5 mAh g −1 at 50 A g −1 ). In addition, with a high mass loading (6 mg cm −2 ), the electrode still displayed a stable capacity (412 mA h g −1 1 A g −1 ). The fast electron transfer and Na + ion diffusion kinetics creates the excellent electrochemical properties, on account of the uniform arrangement of nanoparticles and unique reticular crosslinking structure of CoSe2 /C@GNS. This strategy could also be constructed other electrode materials, which provides more probabilities for the development of SIBs. Graphical abstract: Image 1